Biodiversidade e nível de infestação das moscas-das-frutas (Diptera: Tephritidae) na mesorregião do Agreste paraibano - Sousa, Nayana Rodrigues de (2023)
Fruit flies are the main pests of fruit production worldwide, especially individuals of the Tephritidae family. In this, the genus Anastrepha comprises the species with the greatest economic impact in the Neotropical region. The species Ceratitis capitata is an exotic species and the only representative of its genus in Brazil. Due to its importance and the lack of studies in the region, the objective of this work was to register the assemblage of tephritids in the Mesoregion of the Agreste of Paraiba, as well as to characterize the populations through different faunal indices, fruit infestation and parasitism. For this, mature soil and plant fruits were obtained from monthly collections in orchards in 16 municipalities, in which PET bottle traps were also placed to monitor adults using 5% hydrolyzed protein as a food attractant. The evaluated parameters were diversity and infestation indices. A total of 9.472 specimens were collected from fruits and traps and 14 species belonging to the genus Anastrepha were identified, in addition to the species Ceratitis capitata. 2.770 adults of Anastrepha spp. and Ceratitis capitata in the collected fruits. Infestation rates were evaluated in 10 plant species, with 12.305 fruits collected with 9.691 pupae. The highest levels of infestations were observed in cajá, acerola and seriguela cultures and the parasitoids found belong to the Braconidae family. The research records for the first time the species Anastrepha manihoti in the Agreste Mesoregion of Paraíba: Accidental species predominated, of which the most abundant was Anastrepha fraterculus.